2019
DOI: 10.1038/s41598-019-47314-1
|View full text |Cite
|
Sign up to set email alerts
|

Defective hierarchical porous copper-based metal-organic frameworks synthesised via facile acid etching strategy

Abstract: Introducing hierarchical pore structure to microporous materials such as metal-organic frameworks (MOFs) can be beneficial for reactions where the rate of reaction is limited by low rates of diffusion or high pressure drop. This advantageous pore structure can be obtained by defect formation, mostly via post-synthetic acid etching, which has been studied extensively on water-stable MOFs. Here we show that a water-unstable HKUST-1 MOF can also be modified in a corresponding manner by using phosphoric acid as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 55 publications
1
47
0
Order By: Relevance
“…(Figure 4) In each composite for which significant reaction/modification (based on IR, BET, and EDS measurements) occurred, significant changes in the intensity are seen in the very low diffraction angle MOF peaks. The modified materials show a sharp increase in the ratio of the (002) peak to the (111) peak, based on literature peak assignments, 19,24 consistent with our observation of the etching-and-recrystallization phenomenon seen in Figure 3. Smaller monomers EDOT and 3MOT result in a near-complete disappearance of the (111) peak, while this peak is still seen with significant intensity in the bulkier hexyloxy monomer 3HOT.…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…(Figure 4) In each composite for which significant reaction/modification (based on IR, BET, and EDS measurements) occurred, significant changes in the intensity are seen in the very low diffraction angle MOF peaks. The modified materials show a sharp increase in the ratio of the (002) peak to the (111) peak, based on literature peak assignments, 19,24 consistent with our observation of the etching-and-recrystallization phenomenon seen in Figure 3. Smaller monomers EDOT and 3MOT result in a near-complete disappearance of the (111) peak, while this peak is still seen with significant intensity in the bulkier hexyloxy monomer 3HOT.…”
Section: Methodssupporting
confidence: 91%
“…Both species have the capacity to etch the lattice by protonation of linker ends and introduction of Cu(I) defects respectively. 19,20 The partially degraded HKUST-1 is recrystallized by heating, resulting in full conversion to the more stable 21 hexagonal form with a largerproportion of the (111) face. The barrier to annealing of HKUST-1 is likely reduced by the presence of defects introduced during the monomer/MOF reaction, which accounts for the structural change during heating.…”
Section: Resultsmentioning
confidence: 99%
“…18 SEM of the intermediate material, (Figure 3, top) in which monomer was loaded but not yet heat-treated, suggests an explanation for this conversion. Visibly etched octahedral crystals can be seen in the micrographs of the 19,20 The partially degraded HKUST-1 is recrystallized by heating, resulting in full conversion to the less stable 21 orthorhombic form with a smaller proportion of the {111} face. The barrier to annealing of HKUST-1 is likely reduced by the presence of defects introduced during the monomer/MOF reaction, which accounts for the structural change during heating.…”
Section: Resultsmentioning
confidence: 99%
“…SEM analysis of these samples revealed that the typical morphology of normal Zn-MOF-74 is octahedral with smooth faces, while Zn-MOF-74 in scCO2 shows a similar morphology but with very rough faces (Figure 2b), which might be due to an acidic etching effect of the CO2 at 75 bar and 40 °Ϲ for 72 h. Effect of the acid etching on surface roughness have been previously investigated on amorphous silica and ceramic [68,69]. In addition, etching of MOFs in aqueous acidic solutions such as a mixture of hydroquinone and MeOH (up to 180 °Ϲ for 72 h) or a mixture of phosphoric acid, MeOH and DMSO (at 40 °Ϲ for up to 10 days) has been shown to result in remarkable effects such as interconnected geometrical macropores and etched hole features [37,51,70]. The use of DMSO in BTC to form hydrogen-bonded complexes as reported in the HKUST-1 synthesis [47] was extended to the Zn-BTC.…”
Section: Using Scco2 In Precursor Solution Type Imentioning
confidence: 99%
“…However, by changing to hydrogen-bonded complexes (using dimethyl sulfoxide (DMSO) instead of dimethylformamide (DMF) to form a precursor solution in HKUST preparation), Doan et al reported that the formation of the MOF occurred before additional macropores were introduced by scCO 2 . The latter synthesis can be related to the etching mechanism, which was further studied using different acidic agents [36,37,51]. In addition, use of scCO 2 as an anti-solvent (i.e., a solvent in which the crystals are less soluble) to trigger nucleation from a MOF stock solution [47] was shown to remove the need for the 50-times excess of methanol antisolvent used in the original syntheses [52].…”
Section: Introductionmentioning
confidence: 99%